Three new species of Myrcia sect. Myrcia (Myrtaceae) from South America - Dos Santos, Leidiana Lima; Vasconcelos, Thaís Nogales Da Costa; Sales, Margareth Ferreira De; Lucas, Eve (Phytotaxa, 2021)
Three new species of Myrcia are described, illustrated and discussed. Myrcia rionegrensis from the Brazilian Amazon is related to M. clusiifolia from which it differs in having leaves with acute apex and ribbed fruits (vs. rounded apex and smooth fruits in M. clusiifolia); Myrcia microcalyx is similar to Myrcia scytophylla but differs in having pubescent staminal ring and ellipsoid fruits (vs. glabrous staminal ring and globose fruits in M. scytophylla) and Myrcia peruviana is related to M. riverae, but differs in having smaller leaves and flower buds and ellipsoid fruits (vs. globose in M. riverae).